(untitled) (Global Conference on Medical and Health Sciences, 2026)
Many clinical studies have proven that high cholesterol and corresponding triglycerides increase the risk of coronary diseases. According to WHO and National Statistics, cardiovascular disease accounted for 55-60% of the total causes of death in Central Asian countries: in Uzbekistan, IHD was detected in 5-7% of the adult population, and cardiovascular diseases accounted for up to 60% of the total number of deaths. The following factors influence the spread of cardiovascular disease among the population of the Fergana Valley: urbanization, low physical activity, improper high-calorie diet, stress factors, in some local studies hypertriglyceridemia has been found to be around 30-35% and IHD 10-15%.